1996
DOI: 10.1016/s0896-6273(00)80187-7
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Cells Internalize Aggregates of the Alzheimer's Disease Amyloid β-Protein Via a Scavenger Receptor

Abstract: Microglia are immune system cells associated with Alzheimer's disease plaques containing beta-amyloid (A beta). Murine microglia internalize microaggregates of fluorescently labeled or radioiodinated A beta peptide 1-42. Uptake was confirmed using aggregates of unlabeled A beta detected by immunofluorescence. Uptake of A beta was reduced by coincubation with excess acetyl-low density lipoprotein (Ac-LDL) or other scavenger receptor (SR) ligands, and Dil-labeled Ac-LDL uptake by microglia was blocked by excess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
482
3
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 623 publications
(501 citation statements)
references
References 62 publications
14
482
3
2
Order By: Relevance
“…Consistent with a mechanism involving membrane receptors, we have shown that the lectin ConA, which forms clusters of membrane glycoproteins on the cell surface, also causes neurodegeneration and apoptotic death in cultured neurons similar to that observed with A␤ while succinyl ConA, which binds but does not cross-link, is inactive (39). Recently, Burdick,et al (40) have shown that a substantial portion of the A␤ that binds to cells can be removed by treatment with trypsin and several receptors that appear to bind A␤ peptides have been identifed (41)(42)(43)(44)(45)(46). In the case of the receptor for advanced glycation end products (RAGE), some evidence has been presented that it may be directly involved in A␤-induced neurotoxicity (45).…”
Section: Discussionmentioning
confidence: 74%
“…Consistent with a mechanism involving membrane receptors, we have shown that the lectin ConA, which forms clusters of membrane glycoproteins on the cell surface, also causes neurodegeneration and apoptotic death in cultured neurons similar to that observed with A␤ while succinyl ConA, which binds but does not cross-link, is inactive (39). Recently, Burdick,et al (40) have shown that a substantial portion of the A␤ that binds to cells can be removed by treatment with trypsin and several receptors that appear to bind A␤ peptides have been identifed (41)(42)(43)(44)(45)(46). In the case of the receptor for advanced glycation end products (RAGE), some evidence has been presented that it may be directly involved in A␤-induced neurotoxicity (45).…”
Section: Discussionmentioning
confidence: 74%
“…We propose that failure of microglia to stem the tide of neuronal degeneration and Aβ deposition in AD is the result of the concomitant overexpression of cytokines, such as IL-1, which not only set in motion neurodegenerative cascades but also induce further microglial activation. The inability of microglia to sufficiently clear debris in AD, including fDNA as shown here, may be responsible, at least in part, for the apparently continuous activation of microglia, overexpressing IL-1, in AD, thus ensuring a constant source of cytokines and other factors that foster neurodegeneration (Barger and Harmon, 1997;Giulian et al, 1995;Li et al, 2000;Meda et al, 1995;Paresce et al, 1996). Our finding that some microglia had TUNEL-positive cytoplasm as well as TUNEL positive-nuclei suggests that activation of microglia, together with the act of taking up fDNA, leads to the death of microglia.…”
Section: Discussionmentioning
confidence: 94%
“…Multiple scavenger microglial receptors are proposed mediators of such clearance as they promote microglial adhesion to fibrillar Aβ-containing surfaces (El Khoury et al, 1996) and ingestion of Aβ (Paresce et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-aggregated A␤ can be modestly phagocytosed by microglial class A scavenger receptor and the class B scavenger receptors B1 and CD36 [5,8,9,42,50], but when opsonized, it is more aggressively phagocytosed by Fc receptors and complement receptors [53]. Phagocytosis activates the cells, and A␤ binding to the RAGE (receptor for advanced glycation end-products) is also a powerful activator of microglial inflammation [69].…”
Section: Microglia As Phagocytesmentioning
confidence: 99%